Implementation of Menstrual Leave Rights for Female Workers in Gorontalo under Law No. 13/2003 - Chantika Mobilingo; Weni Almoravid Dungga (Universitas Negeri Gorontalo, 2025)
This study aims to analyze the implementation of menstrual leave rights for female workers in Gorontalo City based on Law No. 13 of 2003 concerning Manpower, focusing on the sociocultural challenges and reproductive health impacts affecting the fulfillment of this right. This research uses a descriptive qualitative approach through observations, interviews, and document analysis of cross-sector companies. The results show a significant gap between the normative provisions outlined in the legislation and the practices on the ground, where menstrual stigma, low socialization, and limited legal understanding among workers and management are major barriers. Additionally, the lack of a supportive work environment and complex administrative mechanisms further hinder women’s access to menstrual leave rights. Some companies view menstrual leave as an additional operational burden and often overlook the substance of female reproductive health protection. Therefore, breakthroughs are needed in the form of continuous education, harmonization of leave application procedures, and more intensive monitoring and law enforcement to ensure optimal implementation of menstrual leave rights. Thus, it is expected to create a more inclusive, fair, and competitive work environment, strengthening the role of women in sustainable regional economic development.